Conectividade funcional e alterações clínicas e cognitivas em uma amostra de afrodescendentes com esquizofrenia e transtorno bipolar - Freitas, Mariélia Barbosa Leal de (2024)
Introduction: Resting state functional magnetic resonance imaging (Rs-fMRI) has advanced research on patients with bipolar disorder (BD) and schizophrenia (SZ), highlighting abnormalities in brain connectivity and specific networks, with emphasis on altered functional connectivity in default mode network (DMN), frontoparietal network (FPN), and salience network (SN). The objective of this research was to correlate Rs-fMRI findings of the functional connectivity of cognitive networks and clinical and cognitive symptoms and early traumatic experiences in a sample of Afro-descendants (blacks) and indigenous people. Materials and methods: The research sample comes from an extension of the partnership with Brazil of the Genetic Cohort in Psychiatry (GPC) study, in the Northeast region, state of Maranhão. Composed of 62 individuals with SZ (n=20), BD (n=21) and tall controls (HC, n=21) of African and indigenous ethnicity. Cognitive, clinical tests (Di-PAD), early trauma scale (ETISR-SF) and Liebowitz social anxiety (LSAS) were applied. Functional assessment carried out using magnetic resonance imaging. Results: Important negative correlation between global efficiency (GE) in the right default mode network and the items mania, irritable mood and racing thoughts in the BD group; Negative correlation of GE in the right dorsal attention network (DAN) and the item psychosis/hallucinations in the SZ group; Physical punishment item (ETISR-SF) and deactivation of the left FPN in SCZ. Conclusion: The process of activation and/or deactivation of the DMN, FPN, DAN and limbic administrative networks were correlated with symptoms of psychosis, mood changes, history of physical punishment and earlier development of schizophrenia and bipolar disorder. The early manifestation of mental disorder and exposure to childhood trauma is related to the dysfunction of electrical networks. Since most studies are with Caucasian and Asian samples, our study adds data on Afro-descendant and indigenous ethnic groups, groups that are underrepresented in research on this topic.